2022
DOI: 10.3389/fimmu.2022.865973
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Responses by Respiratory Viruses, Including Rhinovirus, During Asthma Exacerbation

Abstract: Viral infection, especially with rhinovirus (RV), is a major cause of asthma exacerbation. The production of anti-viral cytokines such as interferon (IFN)-β and IFN-α from epithelial cells or dendritic cells is lower in patients with asthma or those with high IgE, which can contribute to viral-induced exacerbated disease in these patients. As for virus-related factors, RV species C (RV-C) induces more exacerbated disease than other RVs, including RV-B. Neutrophils activated by viral infection can induce eosino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 128 publications
0
14
0
Order By: Relevance
“…( 71 ). In this regard, it seems that human rhinovirus can induce or exacerbate asthma in infected hosts by changing the expression and/or production of inflammatory and pro-inflammatory mediators, which is a point worth considering ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 71 ). In this regard, it seems that human rhinovirus can induce or exacerbate asthma in infected hosts by changing the expression and/or production of inflammatory and pro-inflammatory mediators, which is a point worth considering ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory viral infections, including RSV, in uenza virus, in uenza virus, and parain uenza virus infections, are greatly associated with asthma exacerbation that subsequently leads to wheezing and reduced expiratory ow rate 13,14 . Similarly, our study indicated a high incidence of RSV infection among asthma patients with acute upper respiratory viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Viral respiratory infections, particularly with the rhinovirus (RV) and the respiratory syncytial virus (RSV), are major causes of asthma development and exacerbations ( 79 , 80 ). EVs offer new insight into the viral-induced chronic sequelae in the lung microenvironment.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%